Scarless Cas9 Assisted Recombineering (no‐SCAR) in Escherichia coli, an Easy‐to‐Use System for Genome Editing. Issue 1 (13th February 2018) - Reisch, Christopher R.; Prather, Kristala L.J.
Abstract: The discovery and development of genome editing systems that leverage the site‐specific DNA endonuclease system CRISPR/Cas9 has fundamentally changed the ease and speed of genome editing in many organisms. In eukaryotes, the CRISPR/Cas9 system utilizes a "guide" RNA to enable the Cas9 nuclease to make a double‐strand break at a particular genome locus, which is repaired by non‐homologous end joining (NHEJ) repair enzymes, often generating random mutations in the process. A specific alteration of the target genome can also be generated by supplying a DNA template in vivo with a desired mutation, which is incorporated by homology‐directed repair. However, E. coli lacks robust systems for double‐strand break repair. Thus, in contrast to eukaryotes, targeting E. coli chromosomal DNA with Cas9 causes cell death. However, Cas9‐mediated killing of bacteria can be exploited to select against cells with a specified genotype within a mixed population. In combination with the well described λ‐Red system for recombination in E. coli, we created a highly efficient system for marker‐free and scarless genome editing. © 2017 by John Wiley & Sons, Inc.